Mental Workload Analysis of PMM Outbound Student Using Defence Research Agency Workload Scale (DRAWS) Method - Halwa Annisa Khoiri; Wildanul Isnaini; Putri Cahyaningtyas (OPSI, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) program provides opportunities for students to develop their abilities. One of the MBKM program is Pertukaran Mahasiswa Merdeka (PMM). This program provides option for students to attend lectures at other universitie, so the student can get experience regarding new experience. However, in other hand this program causes mental burden for students who join it. This is because the credits become greater. This study evaluates how the mental workload felt by students using DRAWS method. The results of this study, the most dominant indicator in PMM at PTN is Central Demand and in PTS is Time Pressure. Students who fall into overload category are 60% for PMM in PTN and 59% in PTS. Based on the results, the recommendations that can be given are improving time management for students and review how the policies about PMM so the students are not burden of credits.